Aplikasi Pupuk Kandang Kotoran Ayam Pada Penyetekan Kunyit Putih - Nurul Istiqomah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2013)
White Turmeric is one of the traditional drug known to inhibit the proliferation of cancer cells and have a variety of other benefits . Turmeric can grow well in soil that is loose, fertile , containing organic matter , and has good drainage. Manure is an organic fertilizer that is derived from livestock manure , either in the form of solids ( feces ) that mixed food waste , or urine (urine) , have the ability to improve the physical, chemical , and biological properties of soil .The purpose of this study was ( 1 ) to determine the effect of chiken manure application on white turmeric cutting, and ( 2 ) to determine the best dose of chicken manure on white turmeric cutting . This research has been conducted in the Murung Asam’s village, District of Sungai Pandan from March until June 2012. The design used in this study was a randomized block design consisting of 5 levels of Chicken manure ie p0 (0 g) , p2 (250 g) , p2 (500 g) , p3 (750 g) and p4 (1000 g). The results of the study of chicken manure application has significant effect on the rate of growth of buds , length of buds , number of leaves and the percentage grows .